Creep of Fly Ash Concrete under Sulfate Attack Based on Consolidation Theory and Damage Theory. Issue 2 (April 2021) - Cao, Jian; Xiao, Junjie; Han, Ziyang; Xu, Bin
Abstract: This paper focuses on the creep characteristics of fly ash concrete corroded by sulfate. Firstly, based on the existing research, combined with the creep consolidation theory of concrete, the creep prediction model of fly ash concrete suitable for corrosive environment is analyzed. Secondly, through the analysis of the progress of sulfate corrosion of fly ash concrete, the concept of damage degree in damage theory is introduced to establish the creep calculation model of sulfate corrosion of fly ash concrete. Finally, the calculated value of the model is compared with the test value. The results show that the calculated value of the model is in good agreement with the experimental data and are consistent with the creeping growth trend.